Effect of olfactory bulbectomy on plasma levels of glucose, lipids and corticosterone in the rat (Revista Española de Fisiología, 1984)
The effect of bilateral olfactory bulbs removal on the peripheral glucose, lipids and corticosterone levels has been studied in Wistar male rats.After 30 days of the olfactory bulbectomy there was found: an increase in the basal values of plasmatic glucose, a significant increase in peripheral levels of the free fatty acids, and a notorius decrease in plasmatic corticosterone at 9 a.m.Other biochemical parameters, such as free glycerol, triglycerides and phospholipids, went unaltered.These after bulbectomy variations, especially the increase in free fatty acids, are discussed in relation to a possible role of the olfactory bulbs on the nutritional, endocrine and nervous factors, which are closely related to the mechanisms involved in the regulation of cellular lypolisis.